Association between prehospital physician clinical experience and discharge at scene – retrospective cohort study - Romain Betend; Laurent Suppan; Michele Chan; Simon Regard; François Sarasin; Christophe A. Fehlmann (Swiss Medical Weekly, 2023)
BACKGROUND: Clinical experience has been shown to affect many patient-related outcomes but its impact in the prehospital setting has been little studied.